If $f(n)=\Omega(g(n))$ and $h(n)=\theta (g(n))$ then does this implies $f(n).g(n)=\Omega(g(n).h(n))$

I saw a proof where they have proved If $f(n)=O(g(n))$ and $h(n)=\theta (g(n))$ then this implies $f(n).g(n)=O(g(n).h(n))$.

So I thought may this should also hold. I have taken some examples and the formula holds on all of them. However I can't be sure. There can be a contradicting case.

  • $\begingroup$ Use the definitions. $\endgroup$ – Raphael Dec 31 '17 at 9:34

I have got the answer. It's easy.

Since $f(n)= \Omega g(n)$

$cg(n)\le f(n)$

Multiplying both sides by h(n)



  • $\begingroup$ The penultimate inequality depends on whether $h(n)\ge 0$. In addition, the right hand side is $f(n)h(n)$ while the left hand side of the last equality is $f(n)g(n)$. $\endgroup$ – xskxzr Mar 1 '18 at 14:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.